Chimpanzee genomic diversity reveals ancient admixture with bonobos - de Manuel, Marc (Science, 2016)
Our closest living relatives, chimpanzees and bonobos, have a complex demographic history. We have analyzed the high-coverage whole genomes of 75 wild-born chimpanzees and bonobos from ten countries in Africa. We find that chimpanzee population sub-structure makes genetic information a good predictor of geographic origin at country and regional scales. Most strikingly, multiple lines of evidence suggest that gene flow occurred from bonobos into the ancestors of central and eastern chimpanzees between 200 and 550 thousand years ago (Kya), probably with subsequent spread into Nigeria-Cameroon chimpanzees. Together with another possibly more recent contact (after 200 Kya), bonobos contributed less than 1% to the central chimpanzee genomes. Admixture thus appears to have been widespread during hominid evolution.